# SOLUTION: Solve the system of equations. 7x + 7y + z = 1 x + 8y + 8z = 8 9x + y + 9z = 9

Algebra ->  Algebra  -> Equations -> SOLUTION: Solve the system of equations. 7x + 7y + z = 1 x + 8y + 8z = 8 9x + y + 9z = 9       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Equations Solvers Lessons Answers archive Quiz In Depth

 Question 44504: Solve the system of equations. 7x + 7y + z = 1 x + 8y + 8z = 8 9x + y + 9z = 9 Answer by AnlytcPhil(1277)   (Show Source): You can put this solution on YOUR website!```7x + 7y + z = 1 x + 8y + 8z = 8 9x + y + 9z = 9 1. Pick two equations and pick a letter to eliminate. 2. Eliminate that letter from the two equations you picked. 3. Pick two other equations and eliminate the SAME LETTER that you eliminated in step 2. 4. Now you have two equations in two unknowns. 5. Solve that system in two unknowns. You will have values for two of the three unknowns. 6. Substitute these values into one of the original equations to find the third letter, the one you eliminated in step 1. 1. Pick two equations and pick a letter to eliminate. 7x + 7y + z = 1 x + 8y + 8z = 8 9x + y + 9z = 9 I will arbitrarily pick the first and third equations and the letter y to eliminate. 2. Eliminate that letter from the two equations you picked. Multiply the first by -1 and the second by 7: -1[7x + 7y + z = 1] 7[9x + y + 9z = 9] -7x - 7y - z = -1 56x + 7y + 63z = 63 ------------------- 49x + 62z = 62 3. Pick two other equations and eliminate the SAME LETTER that you eliminated in step 2. I will now pick the first and second equations. I must eliminate the same letter y to eliminate. Multiply the first by -1 and the second by 8: x + 8y + 8z = 8 9x + y + 9z = 9 -1[ x + 8y + 8z = 8] 8[9x + y + 9z = 9] -x - 8y - 8z = -8 72x + 8y + 72z = 72 ------------------- 71x + 64z = 64 4. Now you have two equations in two unknowns. 49x + 62z = 62 71x + 64z = 64 5. Solve that system in two unknowns. Eliminate x by multiplying the first equation by -71 and the seciond equation by 49 -71[49x + 62z = 62] 49[71x + 64z = 64] -3479x - 4402z = -4402 3479x + 3136z = 3136 ---------------------- -1266z = -1266 z = 1 Substitute z = 1 into 49x + 62z = 62 49x + 62z = 62 49x + 62(1) = 62 49x + 62 = 62 49x = 0 x = 0 You now have values for two of the three unknowns. 6. Substitute these values into one of the original equations to find the third letter, the one you eliminated in step 1. Substitute z = 1 and x = 0 into the third original equation 9x + y + 9z = 9 9(1) + y + 9(0) = 9 9 + y + 0 = 9 9 + y = 9 y = 0 Solution: (x, y, z) = (0, 0, 1) Edwin```